Kasih Tanpa Syarat dari Yesus Kristus dan Penghargaan Positif Tanpa Syarat dari Carl Rogers bagi Generasi Z - Krisostomus Amzal Rumadjak; Henderikus Dasrimin (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
This study aims to analyze the correlation between the unconditional love of Jesus Christ and unconditional positive regard according to Carl Rogers and its relevance to the personality development of Generation Z. They live in a digital world with pressures, performative culture, and a high need for validation. The study used qualitative methods. The qualitative method consisted of a literature review of books on Christian theology, humanistic psychology, and related scientific articles, as well as an in-depth questionnaire distribution to six respondents. Six informants from Generation Z experienced struggles with self-identity, social anxiety, and interpersonal relationship dynamics. Data analysis was conducted using a thematic approach to identify recurring patterns of meaning. The results showed that Christ's unconditional love provides a strong spiritual foundation for Generation Z's identity and self-esteem. Both concepts affirm that they are loved unconditionally based on their dignity as God's creations, not on performance or achievement. Meanwhile, Rogers' unconditional positive regard offers a practical psychological framework for personality development, particularly in the development of self-acceptance, empathy, and healthy relationships. This study found that the integration of these two concepts resulted in a comprehensive mentoring model for Generation Z, which helps them manage emotional distress, build authentic relationships, and find their wholeness amidst the intense flow of digitalization. These findings emphasize the importance of dialogue between theology and psychology as complementary approaches in the personality development of the contemporary generation.